FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU LANSIA DALAM KEMANDIRIAN PEMENUHAN KEBUTUHAN AKTIVITAS DAN LATIHAN DI KELURAHAN POTULANDU - Maria Salestina Sekunda (Kelimutu Nursing Journal, 2022)
Everyday activities are all activities done by the elderly every day. This activity is done not through effort or effort. Such activities may be bathing, dressing, eating, or mobilizing. The purpose of this research is to know the factors that influence elderly behaviour in the independence of fulfilling the needs of activities and exercises in Kelurahan Potulando. Type of descriptive research with survey research design. The population of all elderly (age ≥ 60 years old) domiciled in Potulando Urban amounted to 127 people. The sampling technique is purposive sampling, so the number of samples was 38 people. The result showed the factor of age influenced the majority behaviour of respondents (31 people or 82%) in the independence of fulfilment of activity and training needs, physiological health factors influenced the majority behaviour of respondents (25 people or 66%) in independence fulfilment activity requirement and exercises, cognitive function factors did not affect the behaviour of most respondents (35 people or 92%) in the independence of meeting the needs of activities and exercises and family environment factors did not affect the behaviour of some respondents (21 people or 55%) in the independence of meeting the needs of the activity and practice. The result of this research concluded age factor (82%) and physiological health factor (66%) is a factor influencing elderly behaviour in self-reliance in fulfilling activity and training needs in Kelurahan Potulando. It is recommended that health workers always give counselling to the elderly and family about various health problems related to the elderly.